On the Advection of Upwelled Water on the Western Yucatan Shelf - Kurczyn, Jorge. A.; Duran, Rodrigo; Beier, Emilio; Souza, Alejandro J. (Frontiers in Marine Science, 2021)
Upwelling events over the Yucatan Shelf are important physical phenomena within the region. This upwelling process is typical of the summer season and primarily observed on the eastern edge of the Yucatan Shelf, where it is supposed to form and then is transported to the central/northern shelf. The Yucatan upwelling has been studied for some time with a primary focus on its development on the eastern side and its transport to the central part of the Peninsula. There has been very little (or non) effort looking at the impact of this upwelling on the western shelf on the Campeche side. Using a combination of Observations and modeling from 2018 we have found evidence that for the first time upwelled waters are present on the western shelf. Particle tracking integrated back-in-time was used to identify the origin of the upwelled water; our results show that this event brought Subsurface Caribbean Water from the northeast of Yucatan, over 500 km away from the study area. It took over a month to arrive at the study region, traveling along-shelf with an average velocity of 14.5 cm/s, separating the water column into two layers with differentiable thermohaline characteristics. Its trajectories were also observed with climatological Lagrangian Coherent Structures suggesting recurrence. The use of Monthly-averaged SST anomalies shows the presence of upwelled waters off Campeche are persistent mainly during summer (from July to August) each year.